Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/rct.0000000000001350
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Gastrointestinal Neuroectodermal Tumor: A New Kid on the Block?

Abstract: Also referred to as “osteoclast-rich, clear cell sarcoma–like tumor of the gastrointestinal tract (CCSLGT),” malignant gastrointestinal neuroectodermal tumor is a newly described, rare, aggressive sarcoma that commonly arises in the small bowel, stomach, and colon. Histogenesis is likely from an autonomous nervous system–related primitive cell of neural crest origin. The hallmark genetic finding of EWS-CREB1 or EWS-ATF1 fusion transcripts clinches the diagnosis. Annular constrictive lesions tend to be smaller,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…CCSLTGT is a rare malignant soft tissue tumor of the GI tract, which occurs most commonly in young adults. More than 60% of the patients are aged below 45 years, with a median age of 35 years at diagnosis ( 1 ). Patients usually present with abdominal pain, vomiting, abdominal distension, weight loss, and anemia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CCSLTGT is a rare malignant soft tissue tumor of the GI tract, which occurs most commonly in young adults. More than 60% of the patients are aged below 45 years, with a median age of 35 years at diagnosis ( 1 ). Patients usually present with abdominal pain, vomiting, abdominal distension, weight loss, and anemia.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of CCSLTGT is unknown, but some case reports have suggested that a history of radiotherapy may be related to the pathogenesis of the disease ( 4 ). CCSLTGT occurs most commonly in the small bowel wall, but can also occur in the stomach, colon, esophagus, and anal canal ( 1 ). Since a mass originating from the small bowel cannot be detected easily via GI endoscopic examination, CT is a particularly important modality to diagnose CCSLTGT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations